2001
DOI: 10.1007/s005950170067
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Occurrence of Esophageal Cancer After Gastrectomy: A Preliminary Report

Abstract: The effect of gastrectomy on the subsequent development of esophageal cancer was investigated, focusing on its multicentric occurrence. We retrospectively evaluated 28 patients who underwent subtotal esophagectomy for intrathoracic esophageal cancer between 1985 and 1999. They were divided into two groups according to whether or not they had previously undergone a gastrectomy: group 1, comprising 7 patients who had undergone gastrectomy and group 2, comprising 21 patients who had not. Clinical profiles of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Thus, the surgical indication for esophageal cancer has recently been discussed more seriously with respect to its survival benefit [11,12]. There have been many studies concerning esophageal cancers after gastrectomy, which revealed some differences in the clinicopathological features in comparison with esophageal cancer without a history of gastrectomy, such as for sex [13], tumor location [2,5,13], and multiple cancers [14]. However, the survival benefit of surgical therapy for gastrectomized esophageal cancer patients has not been sufficiently discussed, probably because the number of patients in these studies was not adequate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the surgical indication for esophageal cancer has recently been discussed more seriously with respect to its survival benefit [11,12]. There have been many studies concerning esophageal cancers after gastrectomy, which revealed some differences in the clinicopathological features in comparison with esophageal cancer without a history of gastrectomy, such as for sex [13], tumor location [2,5,13], and multiple cancers [14]. However, the survival benefit of surgical therapy for gastrectomized esophageal cancer patients has not been sufficiently discussed, probably because the number of patients in these studies was not adequate.…”
Section: Introductionmentioning
confidence: 99%
“…3 A history of abdominal surgery should not be considered a contraindication to surgery, although esophageal cancer associated with gastric remnants belong to an advanced stage, with a removal rate of 30-50%. 3,5 In our study, one of the strictly selected 28 cases was resected, which related to the case selection. More importantly, with the continuous improvement of auxiliary examination techniques-particularly with the universal application of fiber endoscopy-the early diagnosis of esophageal cancers associated with gastric remnants has become possible, thus increasing the removal rate.…”
Section: Diagnosis Of Esophageal Cancer Associated With Gastric Remnantmentioning
confidence: 99%
“…For extended lymph node metastases, infiltration of adjacent organs, and low rate of early diagnosis, most patients with a history of distal gastrectomy are diagnosed with advanced esophageal cancer; so, their removal rate and survival rate (SR) were lower than in patients without such a history. 5 The reported 5-year overall SR ranged from 7% to 20%, but it was also reported that early detection of esophageal cancer after gastrectomy would lead to longterm SR. 6 This study determines if there is any difference in the clinicopathological features and clinical outcome of esophageal cancer in patients with a history of distal gastrectomy compared with those without such a history.…”
Section: Introductionmentioning
confidence: 96%
“…Some authors reported that it is only incidental [5] , however some experimantal studies demonstrated that carcinogenetic effects of the reflux of gastroduodenal contents on the esophagus is frequently observed after gastrectomy [6,7] . Kitayabashi et al reported that gastrectomy may precipitate chronic gastroesophageal reflux and it can induce the development of squamous dysplasia and carcinoma [8] . This effect may be considered for our patient.…”
Section: Esophageal Carcinoma In a Pregnant Woman Who Has Prior Histomentioning
confidence: 99%